Gut microbiome differences in individuals with PTSD compared to trauma-exposed controls: a systematic review - Winder, Chantelle; Lodhia, Ami; Basso, Melissa; Cohen Kadosh, Kathrin (Frontiers in Neuroscience, 2025)
Post-traumatic stress disorder (PTSD) is a common mental health disorder that can occur following exposure to a traumatic event, and is characterized by symptoms including intrusive memories, dissociation, and nightmares. PTSD poses significant suffering on the individual and can reduce quality of life substantially, however, its mechanisms are not fully understood. It has also been associated with gut abnormalities, such as with irritable bowel syndrome, indicating possible involvement of the gut microbiome and gut-brain axis. Whereas previous research has implicated the gut microbiome and microbiome gut-brain axis in various mental health disorders, the relationship between gut microbiome function and PTSD is unclear. Specifically, little is known about whether specific gut microbiome compositions can increase the risk of developing PTSD, or, vice versa, act as a protective factor for the individual. This systematic review aims to synthesize the literature looking at gut microbiome differences between individuals with PTSD and trauma-exposed controls (TEC) while exploring potential risk and resilience factors for development of the disorder. Three studies met the inclusion criteria, and results showed that all studies found differences in gut microbial taxa between PTSD and TEC groups yet varied in their taxonomic level and type. One study found a significant difference in diversity between groups, reporting lower diversity in PTSD, and two studies found certain taxa to be correlated with PTSD symptom severity: Mitsuokella, Odoribacter, Catenibacterium and Olsenella genera, and Actinobacteria, Lentisphaerae and Verrucomicrobia phyla. This review has important implications for potential novel treatments for PTSD which target the gut microbiome, for example psychobiotic dietary interventions such as prebiotics and probiotics. It also informs our understanding of potential risk and resilience factors for the disorder, such as certain gut microbiome compositions being potentially protective or increasing susceptibility. More research is needed, as currently sample sizes are small and confounding variables (e.g., diet) are not always controlled for.Systematic review registration: The protocol was registered on PROSPERO, registration number: CRD42024530033.